Impact of Sexual Assault Survivor Identity on Patient Care in the Emergency Department. Issue 3 (February 2023) - Chalmers, Kristen; Parameswaran, Ramya; Dussault, Nicole; Farnan, Jeanne; Oyola, Sonia; Carter, Keme
Interactions between emergency department (ED) staff and sexual assault (SA) survivors can be a source of retraumatization for survivors, increasing their risk of posttraumatic stress and decreasing utilization of longitudinal medical care. Little is known about nationwide trends in ED staff attitudes and behaviors toward survivors, including the impact of survivor identity. We conducted a survey to determine if survivor identity influenced ED staff behaviors. A nationwide survey of SA patient advocates was conducted between June and August 2021. Advocates are volunteers or staff dispatched from rape crisis centers to support survivors during ED care. Advocates participated in an online survey to determine the frequency of observing six potentially retraumatizing provider attitudes and behaviors. Adaptive questioning was used to explore the impact of survivor identity on each attitude or behavior and which identity groups were more likely to be affected. Three hundred fifteen advocates responded to the survey. Less than 10% indicated that ED staff often or always convey disbelief or blame to survivors. Almost 75% of advocates indicated that they often or always observe ED staff showing empathy to survivors. Disparities were found in provider attitudes. Over 75% of advocates observed that survivors' mental health status or substance use impacted conveyed belief from providers. Patients who were intoxicated when assaulted, had psychiatric disorders, were Black, Hispanic/LatinX, or indigenous, or were not cis-females were more likely to experience disbelief. Patients who were white and/or cis-gender females were more likely to be pressured by ED staff to complete the forensic exam and/or report to the police. Our study documents disparities in ED staff behavior towards SA survivors according to survivor identity. Given that post-assault ED interactions are critical turning points in survivors' future medical processes, disparities in ED care may be linked to larger disparities in healing from trauma.